ANALISIS POTENSI DESA PANAMBANGAN KABUPATEN CIREBON SEBAGAI DESA WISATA BERBASIS PARTICIPATORY MAPPING - niamillah, kholishotun; Alfian, Rizki; Soelistyari, Hesti Soelistyari Triana (Universitas Tribhuwana Tunggadewi, 2025)
Panambangan Village has been designated as a tourist village in Cirebon Regency; however, its potential has not been optimally managed due to a lack of comprehensive planning. The purpose of this study is to analyze the potential of Panambangan Village and formulate recommendations for its development concept as a community-based tourism village. The research method employed is a descriptive qualitative approach, with a special emphasis on participatory mapping, which was implemented through focus group discussions (FGDs). This research process consists of three main stages: potential inventory, analysis, and formulation of recommendations. The results showed that Panambangan Village has significant potential, including natural attractions such as mountain views, rice fields, and rivers, supported by good environmental quality, as well as cultural potential. Basic infrastructure is adequate for supporting tourism, and the other side infrastructure, such as transportation and accommodation access, still requires improvement. The culmination of this research, through participatory mapping activities, successfully mapped the village's potential points, which were then grouped into three recommended development zones: the revitalization zone, the settlement zone, and the cultural zone.